Installation of gussets to reduce stress on the junction between the arm and bridge on the swing arm - Hidayat, Nailul; A, Yufrizal; Nurdin, Hendri; Kassimov, Farid; Kenzhaliyev, Elnar (Journal of Engineering Researcher and Lecturer, 2023)
The swing arm is one of the main components of a motorcycle that functions as a connection between the rear wheel and the frame. Under loading conditions, the joint area between the arm and the bridge experiences significant stress, leading to fractures in that region. This study aims to investigate the effectiveness of installing gussets to reduce the stress that occurs at the joint area between the arm and the bridge in the swing arm of ELGO electric motorcycles. The research was conducted using the static analysis simulation method with Solidworks 2021-2022 Research License software. The loading conditions were simulated based on the actual usage of the electric motorcycle. The simulation results revealed that without the installation of gussets, the joint area between the arm and the bridge in the swing arm experienced stress exceeding the yield strength of the material. This would inevitably lead to the breakage of the swing arm and potentially cause accidents for motorcycle riders. However, after the gussets were installed, the stress at the joint area between the arm and the bridge remained below the yield strength of the material. Based on these findings, it can be concluded that the installation of gussets successfully reduced the stress at the joint area between the arm and the bridge in the swing arm. This research outcome can serve as a reference for the design of swing arms for electric motorcycles.